Design and implementation of virtual reality instructional tools for 3D printing processes in digital manufacturing - Daniel Cubillos; Magesh Chandramouli (Journal of Intelligent Manufacturing and Special Equipment)
Purpose – In order to allow easy replication of this study, industry standard software that is easily attainable was used. Most of the programs used are free to download, and the ones that are not are available, students can still obtain them through their university or free download options for enrolled university students. There is also a large online community for new users to learn how to use the programs through online tutorials, message boards and free instructional material provided by the developers. As this paper expands on the work created during part 1, the models and information gathered for SLA, SLS and FDM processes were modified and updated in order to be used for the second phase. The models were created using 3ds Max, an industry standard 3D modeling program created by Autodesk Media and entertainment. All the models, textures and animations were created using 3ds Max. While the program is not free, Autodesk does allow students to download the program for free as long as they are enrolled in an accredited university. It is common for universities to get Autodesk licensing for computer labs if they have a technology program, making it possible for students to use the program through the university. Design/methodology/approach – The VR system chosen was the Dell Visor: it offered the best combination of software support through SteamVR and Unity compatibility, low cost compared to other currently available VR systems, along with hardware and software requirements that could be met relatively easily (Chandramouli et al., 2018; Chandramouli et al., 2014a). Dell Visor requires 1 HDMI port and 1 USB 3.0 port to connect the headset to the computer, and can work with laptops. Dell Visor uses two hand controllers for movement tracking, Bluetooth connection is used to connect the hand controllers to the headset and computer in order to provide freedom of movement. This small number of ports and connecting wires required for the head set allows easy set up and increased flexibility of movement for the Dell Visor compared to most other VR headsets currently available. Dell Visor is also compatible with most computers, even older models thanks to use of adaptors. With the use of an adaptor and dongle for Bluetooth and HDMI support, even if the computer does not initially meet the hardware requirements of the system, it is still possible to run the Dell Visor on the computer. Findings – The final simulation incorporates aspects of both the process and assembly aspects of the earlier scenes, but presents them using a constraint code added to sliding levers and pieces of the SLA 3D printer that lock into place when assembled. This simulation was created with the intent of being a demo for the capability of VR, as it uses the pre-build SteamVR code that is publicly available for use in Unity. This simulation uses a slide and lock constraint on a lever mechanism that allows the user to manually control the flow of the printer process, by moving the lever left and right, the user can rewind and fast forward through the printer animation as much as they wish to. There is also an assembly table to attach the individual parts of the SLA printer together. The pieces lock into place when put into the correct spot, using the base part of the printer as the starting point for them to build off. Originality/value – While VR technology is still a relatively new field, the possible uses of this technology are becoming better understood in recent years. As both the general public and institutions become better acquainted with VR, more opportunities are created for instruction. VR has been associated with entertainment as the primary use for the technology, however, there is potential for VR in both business and educational as an effective learning tool. The main priority above all else for the simulations created for this study was to teach people about 3D printing in an accurate and interesting manner. Throughout the entire process this end goal was kept in mind, and achieving this goal shows the academic potential of VR for institutions. This study has provided a framework for how an institution can create a customized VR instructional model to fit their student’s needs. Using either freely available or academically partnered programs for use, any university can begin to create their own VR instructional materials that are compatible with both VR headset and desktop. Unity has a large online support network for students to troubleshoot and teach themselves how to use the software; it is compatible with modern computers so it is possible to create simulations that do not require a VR headset, and is free to use. This can allow universities to create simulations for relatively low cost and low barrier to entry, not factoring the initial cost of buying the necessary programs, hardware and time required for new users to learn the software.